A Single Longitudinal Mode Fiber Ring Laser Based on Cascaded Microfiber Knots Filter - Li, Yue (2017)
A single longitudinal mode (SLM) fiber ring laser based on a cascaded microfiber knots filter (CMKF) is proposed and demonstrated. The CMKF is consists of two microfiber knot resonators, which can cause a spatial mode beating interference deriving from high proportional evanescent field of microfiber and spectrum magnification function of Vernier effect, resulting in a passive narrow-band filter with the ability to generate stable SLM. Theoretical analysis and simulation are carried out to investigate the Vernier transmission spectrum of the CMKF and then the SLM principle. A narrow linewidth, high stability, and low-noise SLM lasing with a central wavelength of 1560.6 nm, a 3-dB bandwidth of less than 0.016 nm, and side mode suppression ratio better than 55 dB is achieved experimentally.